Green entrepreneurial orientation and firm performance: do green purchasing and supply chain integration matter? - Emmanuel Kwabena Anin; Daniel Etse; Gilbert Anyowuo Okyere; Darlington Bright Yao Adanfo (Cogent Business & Management, 2024)
Green entrepreneurial orientation (GEO) and green supply chain management (GSCM) have emerged as important strategic tools for environmental management. Integrating the sustainability capabilities of GEO with GSCM practices, such as green purchasing and green supply chain integration, is crucial for optimizing both environmental and commercial outcomes. Yet, how the interface of GEO and GSCM drives corporate environmental and financial performances remains underexplored. We draw on the Natural/Resource Based View to argue that the environmental and financial performance consequences of GEO may be channelled through green purchasing under varying conditions of green supplier and customer integration. We test our model using survey data from 225 SMEs in a sub-Saharan African country. We find a direct positive effect of GEO on the environmental but not on financial performance. Further results reveal that the environmental and financial performance benefits of GEO are more salient when channelled through green purchasing, particularly under greater levels of green supplier and customer integration. The theoretical and practical implications are discussed.
Keywords: 650; Green entrepreneurial orientation; green purchasing; green supplier integration; green customer integration; organisational performance